Penerapan media pembelajaran pop up book untuk meningkatkan keterampilan berbicara siswa di kelas IV SD Negeri Syota - Stelie D Ratumanan; Brian Berti Keiwury; Zainudin Notanubun (COLLASE (Creative of Learning Students Elementary Education), 2026)
This study used a classroom action research (CAR) method. The CAR focused on 10 fourth-grade students at Syota Public Elementary School, Moa District, Southwest Maluku Regency. This study involved two cycles: Cycle I and Cycle II. Data collection techniques included observation, tests, and documentation. Data analysis was conducted in two ways: qualitative data in the form of field notes, interviews, observations, and documentation, and quantitative data. Based on the data obtained, the study was considered successful because all students achieved an increase in grades in accordance with the specified Minimum Competency (KKM), namely 65 on the final test of Cycle II. So it can be explained, 3 students got a score of 70, 70%: 3 students got a score of 80, 80%, 4 students got a score of 90, 90%. Thus it can be said that 10 (100) students got a score of ≥ 65 with an average score of 81.